Evaluation of Antiinflammatory Activity of Marine Omega-3 in Rats - Faizah, Ana Khusnul; Kresnamurti, Angelica (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Marine omega-3 from fish contains high EPA dan DHA which may have an analgesic and anti-inflammatory effects. The objective of study is to analyze the anti-inflammatory effect of marine omega-3 in rats. The method of this study is pre-post control experimental. The acute anti-inflammatory effect of marine omega-3 were investigated through carrageenan induced paw edema in rats. Thirty minutes before the procedure, the experimental groups were treated with fish oil 40 and 60 mg/kg; sodium diclofenac (5 mg/kg) as positive control groups and span 80-tween 80 as negative control groups. The degree of paw edema was measured by caliper. The marine omega-3 showed anti-inflammatory effect in a dose-dependent manner. The results of 60 mg/kg of marine omega-3 was significantly different compared with the negative. Overall, the marine omega-3 has acute anti-inflammatory activity in rats.